2015
DOI: 10.1007/s11604-015-0515-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of 18F-FDG PET/CT for axillary lymph node staging in patients with breast cancer

Abstract: Axillary nodal SUVmax may be a prognostic indicator of disease recurrence in patients with axillary LN metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…However, despite the very high specificities (99.0% and 99.5%) of FDG-PET/CT observed in this study, the sensitivities of the human diagnosis with FDG-PET/CT for axillary LN metastasis were quite poor (59.8% and 57.4%). Similar results have been reported by other groups [3][4][5][6][7][8][9]. To improve the sensitivity, we constructed an AI-assisted diagnosis system.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, despite the very high specificities (99.0% and 99.5%) of FDG-PET/CT observed in this study, the sensitivities of the human diagnosis with FDG-PET/CT for axillary LN metastasis were quite poor (59.8% and 57.4%). Similar results have been reported by other groups [3][4][5][6][7][8][9]. To improve the sensitivity, we constructed an AI-assisted diagnosis system.…”
Section: Discussionsupporting
confidence: 72%
“…All FDG-PET/CT images were retrospectively reviewed by one experienced reader (12 years of experience with oncologic FDG-PET/CT; referred to as clinician A hereinafter) and one reader (2 years of experience with oncologic FDG-PET/CT; referred to as clinician B hereinafter), both of whom had no knowledge of the other imaging results or clinical and histopathologic data other than the presence of breast cancer. Because several groups have reported that the diagnostic performances of qualitative and quantitative assessments were not significantly different [9,12,13], we used a qualitative assessment in this study. The diagnostic certainty of assessing axillary LN metastasis was visually graded as 1 (definitely absent), 2 (probably absent), 3 (indeterminate), 4 (probably present), and 5 (definitely present).…”
Section: Human Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-body 18 F-FDG PET examinations with a CT scanner (Gemini GXL16; Philips Medical Systems, Eindhoven, The Netherlands) were performed at Hyogo College of Medicine Hospital. As described in a previous study [ 25 ], 4.0 MBq/kg body weight of 18 F-FDG was used for PET and the scanning image was obtained approximately 60 min after the injection. The SUV was calculated as the regional radioactivity concentration (Bq/mL)/[injected dose (Bq)/patient’s weight (g)] in the most intense area of 18 F-FDG accumulation (a region of interest: ROI) and the peak SUV in the pixel with the highest count within the ROI was defined as the SUVmax.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, to evaluate their diagnostic ability in this area, other techniques have been tested, such as positron emission sonography, positron emission sonography/ computed tomography, and magnetic resonance imaging. [26][27][28][29] However, a newer sonographic modality has been available for some time now: contrast-enhanced sonography. Thanks to it, we can obtain reference points for the vascularization pattern of a given organ.…”
mentioning
confidence: 99%